The main character’s awareness of death as reflected in Lauren Oliver’s Before I Fall: A psychological approach - Astry Fajria; Aprilia Nilham (UAD TEFL International Conference)
This paper is related to the idea of death as seen in the novel Before I Fall. The major theme is about people's awareness of death from a different perspective. The novel presents a young girl’s interpretation of death when she once confronted with it. The idea of death appears as the most unwanted thing at first and turns out to be something that has to be accepted because it is inevitable. This paper will discuss people’s awareness of death that include fear and anxiety, stages of dying, and personal growth and the implication on human’s life.